IDENTIFICATION OF MOISTURE CONTENT IN THE CLASSIFICATION OF SOLID BULK CARGO OF NICKEL ORE THAT HAS THE POTENTIAL TO LIQUIFY WHILE IN THE CARGO HOLD OF A MERCHANT SHIP - Mariah, Yuni; Busrian, Erin; Aziz , Amalil; Tazkiah, Tazkiah; Zaeni, Nur (PT. Hafasy Dwi Nawasena, 2026)
Iron ore has long been used for industrial steelmaking. Several countries have very large reserves of this commodity, such as Brazil and Australia, which export 70% of their total exports and are the two countries with the highest export value, followed by other countries such as South Africa, Chile, Canada, and the United States with an estimated 33%. Most iron ore is transported by Capesize ships > 80,000 DWT, and even for oceangoing transportation, it can be much larger, reaching 165,000 DWT with a ship length exceeding 350 meters with a draft of over 20 meters. Solid bulk cargo of nickel ore poses a risk in transportation because it can melt (liquefy) during the journey, reducing the stability of the ship, thus endangering the safety of the ship. Solid bulk cargo of nickel ore is classified as cargo group A, which is that it may liquefy if shipped at a moisture content (MC) exceeding the Transportable Moisture Limit (TML). The liquefaction of nickel ore cargo has caused the capsizing of several ships and reduced safety in transportation. To overcome the risk of liquefaction in solid bulk Nickel ore cargo before the start of loading, a laboratory moisture content test must be carried out so that the cargo is safe before being loaded. The purpose of this study is to analyze the moisture content in solid bulk Nickel ore cargo that is at risk of liquefaction and can disrupt the stability of the ship. If the Moisture Content in a Group A cargo exceeds the Transportable Moisture Limit, then the cargo can be declared unsafe to be loaded onto the ship. Therefore, the Moisture Content of the cargo must be reduced to less than the specified Transportable Moisture Limit.